DETERMINATION OF GROUND-LEVEL AIR POLLUTION BY VEHICLE EXHAUST GASES BASED ON CARBON MONOXIDE CONCENTRATIONS - Сандугаш, Абилкасова (Academic Journal of Physical and Chemical Sciences, 2023)
Road transport is one of the sources of environmental pollution. Nowadays, the impact of transport on the environment is the most urgent and pressing problem of modern society. The relevance of the study lies in the fact that adverse environmental factors affect the condition and health of people. A huge role in the formation of atmospheric air pollution is played by emissions of impurities from fuel combustion process. One of the reasons for the increase in the volume of pollutants from exhaust emissions is the growth of the car fleet. The environmental situation is worsened by: poor environmental performance of fuels and vehicles in Kazakhstan, an ageing vehicle fleet and deteriorating maintenance, inadequate road development and deterioration, and underestimation of architectural and planning factors in cities. Carbon dioxide and other gases, which have a greenhouse effect, spread throughout the atmosphere, causing global geo-environmental impacts. The purpose of the research was to determine the impact of automobile exhaust gases on the ecology of the city and to improve the methodology for assessing the environmental and economic damage from chemical pollution by motor vehicle emissions to the environment of Almaty. The levels of ISSN 2224-5227 2. 2023 128 atmospheric air pollution by carbon monoxide on a particular section of the motorway were determined. The coefficient of toxicity of CO emissions into the atmosphere, the background pollution of the surface layer of the atmospheric air, the total traffic intensity of cars on the streets of Almaty, a certain type of cars for CO emissions into the atmosphere; the coefficient taking into account aeration on a given road section and the value of the slope of the roadway; wind speed, air humidity, dependence of carbon monoxide concentration on the type of road crossing were calculated. The research was conducted on control points of emissions of chemical pollutants. The work was carried out in the laboratory of the Department of Chemistry, Chemical Technology and Ecology of Almaty Technological University.